Constitutive Contact Laws in Structural Dynamics - Willner, Kai (Cmes-Computer Modeling in Engineering & Sciences, 2009)
The dynamic behavior of structures with joints is strongly influenced by the constitutive behavior within the contact areas. In this paper the influence of an elaborate constitutive contact model based on a rough surface model is investigated. The contact model is able to describe several effects like pressure dependent contact stiffness in normal and tangential direction as well as microslip effects. The corresponding constitutive contact laws are implemented in a finite element code. Numerical simulations are compared to experimental results of a clamped double-beam experiment. Copyright © 2009 Tech Science Press.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-TM.consti
Keywords: Damping; Friction; Joints; Structural dynamics